Analytical profile of N‐ethyl‐N‐cyclopropyl lysergamide (ECPLA), an isomer of lysergic acid 2, 4‐dimethylazetidide (LSZ). Issue 10 (17th September 2020) - Brandt, Simon D.; Kavanagh, Pierce V.; Westphal, Folker; Stratford, Alexander; Elliott, Simon P.; Dowling, Geraldine; Halberstadt, Adam L.
Abstract: Recent investigations have shown that N ‐ethyl‐ N ‐cyclopropyl lysergamide (ECPLA) produces LSD‐like behavioral effects in mice, which suggests that it may act as a hallucinogen in humans. Although the use of ECPLA as a recreational drug has been limited, key analytical data that can be used to detect ECPLA are required for future forensic and clinical investigations. ECPLA is an isomer of (2′ S, 4′ S )‐lysergic acid 2, 4‐dimethylazetidide (LSZ), a lysergamide that emerged as a recreational drug in 2013. Several analytical approaches were examined, including single‐ and tandem mass spectrometry platforms at low and high resolution, gas‐ and liquid chromatography (GC, LC), nuclear magnetic resonance spectroscopy (NMR), and GC condensed‐phase infrared spectroscopy (GC‐sIR). ECPLA and LSZ could be differentiated by NMR, GC‐sIR, GC, and LC‐based methods. The electron ionization mass spectra of ECPLA and LSZ contained ion clusters typically observed with related lysergamides such as m/z 150–155, m/z 177–182, m/z 191–197, m/z 205–208, and m/z 219–224. One of the significant differences in abundance related to these clusters included ions at m/z 196 and m/z 207/208. The base peaks were detected at m/z 221 in both cases followed by the retro‐Diels‐Alder fragment at m/z 292. Minor but noticeable differences between the two isomers could also be seen in the relative abundance of m/z 98 and m/z 41. Electrospray ionization mass spectra included lysergamide‐related ions at m/z 281, 251, 223, 208, 197, 180, and 140. LSZ (but not ECPLA) showed product ions at m/z 267 and m/z 98 under the conditions used. Abstract : In‐depth characterization of N ‐ethyl‐ N ‐cyclopropyl lysergamide (ECPLA) using various chromatographic, mass spectrometric, and spectroscopic methods including exploration of the analytical features suitable for differentiation between ECPLA and (2′ S, 4′ S )‐lysergic acid 2, 4‐dimethylazetidide (LSZ), an isomeric lysergamide that emerged on the recreational drug market in 2013.